Evaluation of mechanical properties of unsaturated polyester-guar gum/hydroxypropyl guar gum composites (eXPRESS Polymer Letters)
Guar gum is a natural polysaccharide that has been explored for various applications. However, there is a limited number of studies in which guar gum has been used as a filler in a polymer. The effect of guar gum and its hydroxypropyl derivatives in unsaturated polyester composites were investigated with respect to their mechanical and chemical properties. The effect of hydroxypropylation and the degree of hydroxypropylation on the properties of resultant composites were also studied. It was observed that the inclusion of guar gum and its derivatives resulted in composites with increased solvent resistance and mechanical properties. An increase in the degree of substitution resulted in increased polymer-filler interaction reflected by a positive effect on the mechanical properties of the composites. These results open an avenue for the use of polysaccharides and their derivatives as eco-friendly fillers as a replacement of mineral fillers.